2023
DOI: 10.1038/s41467-023-38624-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived chemokines promote skeletal muscle regeneration by guiding neutrophil recruitment to injured muscles

Abstract: Skeletal muscle regeneration involves coordinated interactions between different cell types. Injection of platelet-rich plasma is circumstantially considered an aid to muscle repair but whether platelets promote regeneration beyond their role in hemostasis remains unexplored. Here, we find that signaling via platelet-released chemokines is an early event necessary for muscle repair in mice. Platelet depletion reduces the levels of the platelet-secreted neutrophil chemoattractants CXCL5 and CXCL7/PPBP. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 149 publications
3
19
0
Order By: Relevance
“…[25] Further confirming the important role of neutrophils in muscle regeneration downstream of platelet-induced chemokine signaling, we found that antibody-based depletion of neutrophils similarly reduces myofiber size and muscle force production post-injury. [25] Altogether, this study identifies a key role of platelets in regenerating muscle by guiding the infiltration of neutrophils into injured muscles (Figure 1).…”
Section: Platelet-secreted Chemokines Promote Muscle Regeneration By ...supporting
confidence: 75%
See 4 more Smart Citations
“…[25] Further confirming the important role of neutrophils in muscle regeneration downstream of platelet-induced chemokine signaling, we found that antibody-based depletion of neutrophils similarly reduces myofiber size and muscle force production post-injury. [25] Altogether, this study identifies a key role of platelets in regenerating muscle by guiding the infiltration of neutrophils into injured muscles (Figure 1).…”
Section: Platelet-secreted Chemokines Promote Muscle Regeneration By ...supporting
confidence: 75%
“…Our study now indicates that platelets are necessary to recruit neutrophils to injured muscles and that this occurs via the secretion of platelet‐specific chemokines with potent neutrophil chemoattractant activities. [ 25 ] In particular, we found that neutrophil infiltration, which occurs by day 1 after injury, is significantly reduced by platelet depletion. Cytokine arrays indicate that the intramuscular protein levels of the neutrophil chemoattractants CXCL5 and CXCL7/PPBP, which are chemokines specifically expressed by platelets, [ 27 ] are high at day 1 after injury but that their levels are significantly reduced by platelet depletion.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations